K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

19 tháng 7 2021

`(y+3)^3-(3-y)^2-54y`

`=y^3+9y^2+27y+27-9+6y-y^2-54y`

`=y^3+8y^2-21y+18`

 

Ta có: \(\left(y+3\right)^3-\left(3-y\right)^2-54y\)

\(=y^3+9y^2+27y+27-\left(y^2-6y+9\right)-54y\)

\(=y^3+9y^2-27y+27-y^2+6y-9\)

\(=y^3+8y^2-21y+18\)

a) (x + 3y) (2x2y - 6xy2)

= (x + 3y) + 2xy (x - 3y)

= 2xy [(x + 3y) (x - 3y)]

= 2xy (x2 - 3y2)

b) (6x5y2 - 9x4y3 + 15x3y4) : 3x3y2

= (6x5y2 : 3x3y2) + (-9x4y3 : 3x3y2) + (15x3y4 : 3x3y2)

= [(6 : 3) (x: x3) (y2 : y2)] + [(-9 : 3) (x4 : x3) (y3 : y2)] + [(15 : 3) (x3 : x3) (y4 : y2)]

= 2x2 + (-3xy) + 5y2

= 2x2 - 3xy + 5y2

#Học tốt!!!

5 tháng 11 2019

a) \(\left(x+3y\right)\left(2x^2y-6xy^2\right)\)

\(=x\left(2x^2y-6xy^2\right)+3y\left(2x^2y-6xy^2\right)\)

\(=2x^3y-6x^2y^2+6x^2y^2-18xy^3\)

\(=2x^3y-18xy^3\)

b) \(\left(6x^5y^2-9x^4y^3+15x^3y^4\right):3x^3y^2\)

\(=6x^5y^2:3x^3y^2-9x^4y^3:3x^3y^2+15x^3y^4:3x^3y^2\)

\(=2x^2-3xy+5y^2\)

5 tháng 11 2019

c) \(\left(2x+3\right)^2+\left(2x+5\right)^2-2\left(2x+3\right)\left(2x+5\right)\)

\(=\left(2x+3-2x-5\right)^2\)

\(=\left(-2\right)^2=4\)

d) \(\left(y+3\right)^3-\left(3-y\right)^2-54y\)

\(=y^3+9y^2+27y+27-\left(x^2-6x+9\right)-54y\)

\(=y^3+9y^2-27y+27-x^2+6y-9\)

\(=y^3+9y^2-x^2-21y+18\)

4 tháng 11 2019

a)

b) \(\left(6x^5y^2-9x^4y^3+15x^3y^4\right):3x^3y^2\)

\(=2x^2-3xy+5y^2.\)

c)

Chúc bạn học tốt!

27 tháng 6 2017

Ta có (y-x)^2=(x-y)^2

Nên

(x-y^3:(x-y)^2

=x-y

27 tháng 6 2017

(x-y)3 : -(x-y)2

= -(x-y) = y-x

16 tháng 12 2021

\(\dfrac{3}{2x^2+y}+\dfrac{5}{xy^2+}+\dfrac{x}{y^3}\)

=\(\dfrac{3xy^5}{xy^2.y^3\left(2x^2+y\right)+}+\dfrac{10y^3x^2+5y^4}{xy^2.y^3\left(2x^2+y\right)}+\dfrac{2x^4y^2+x^2y^3}{xy^2.y^3\left(2x^2+y\right)}\)

=\(\dfrac{3xy^5+10y^3x^2+5y^4+2x^4y^2+x^2y^3}{xy^5\left(2x^2+y\right)}\)

=\(\dfrac{3xy^5+11y^3x^2+5y^4+2x^4y^2}{xy^5\left(2x^2+y\right)}\)

 

   ủa đáp án cứ sao sao:<

 

17 tháng 12 2020

MTC = (x - y)(x2 + xy + y2)

\(\dfrac{1}{x-y}-\dfrac{3xy}{x^3-y^3}+\dfrac{x-y}{x^2+xy+y^2}\)

\(=\dfrac{x^2+xy+y^2}{\left(x-y\right)\left(x^2+xy+y^2\right)}-\dfrac{3xy}{\left(x-y\right)\left(x^2+xy+y^2\right)}+\dfrac{\left(x-y\right)^2}{\left(x-y\right)\left(x^2+xy+y^2\right)}\)

\(=\dfrac{x^2+xy+y^2-3xy+\left(x-y\right)^2}{\left(x-y\right)\left(x^2+xy+y^2\right)}\)

\(=\dfrac{x^2+xy+y^2-3xy+x^2-2xy+y^2}{\left(x-y\right)\left(x^2+xy+y^2\right)}\)

\(=\dfrac{2x^2-4xy+2y^2}{\left(x-y\right)\left(x^2+xy+y^2\right)}\)

\(=\dfrac{2\left(x^2-2xy+y^2\right)}{\left(x-y\right)\left(x^2+xy+y^2\right)}\)

\(=\dfrac{2\left(x-y\right)^2}{\left(x-y\right)\left(x^2+xy+y^2\right)}\)

\(=\dfrac{2\left(x-y\right)}{x^2+xy+y^2}\)

16 tháng 12 2020

1/x-y-3xy/x^3-y^3+x-y/x^2+xy+y^2

=1/x-y+-3xy/(x-y)(x^2+xy+y^2)+x-y/x^2+xy+y^2

=x^2+xy+y^2/(x-y)(x^2+xy+y^2)+-3xy/(x-y)(x^2+xy+y^2)+x^2-2xy+y^2/(x-y)(x^2+xy+y^2)

=x^2+xy+y^2-3xy+x^2-2xy-y^2/(x-y)(x^2+xy+y^2)

=2x^2-5xy/(x-y)(x^2+xy+y^2)

20 tháng 8 2021

a) (𝑥−5)(𝑥+7)

𝑥(𝑥+7)−5(𝑥+7)

𝑥2+7𝑥−5(𝑥+7)

𝑥2+7𝑥−5𝑥−35

𝑥2+2𝑥−35

b) (𝑥−3)(𝑥2+5𝑦)

𝑥(𝑥2+5𝑦)−3(𝑥2+5𝑦)

𝑥3+5𝑥𝑦−3(𝑥2+5𝑦)

𝑥3+5𝑥𝑦−3𝑥2−15𝑦

𝑥3−3𝑥2+5𝑥𝑦−15𝑦